Bisphosphonate treatment of benign multifocal and unifocal osteolytic tumours of bone. - Gibbons, C; Petra, M; Smith, R; Athanasou, N (2003)
Growth of benign tumours and tumour-like lesions of bone results in osteolysis which may cause pathological fracture. Bisphosphonates are anti-osteolytic agents which have proved effective in the treatment of number of osteolytic conditions. In this study we report the results of treatment with the aminobisphosphonate, pamidronate, of three benign osteolytic tumours of bone, two cases of fibrous dysplasia and one of Langerhans cell histiocytosis. In all three cases there was clinical and radiological improvement following treatment. Radiologically, bone lesions did not exhibit progressive enlargement. Two cases of fibrous dysplasia also showed features suggestive of increased bone formation. These findings indicate that bisphosphonates are likely to be useful in controlling the osteolysis of benign tumours/tumour-like lesions of bone, particularly in those cases where surgical intervention is not possible or multifocal lesions are present.